Outcome of extremely low gestational age newborns (ELGANs) following a pro-active treatment approach (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: To determine the impact of a pro-active treatment approach on outcome of extremely low gestational age neonates (ELGANs; gestational age [GA]